1976
DOI: 10.1212/wnl.26.9.853
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Z band streaming and myofibrillar disruptions in skeletal muscle from healthy young people

Abstract: Skeletal muscle tissue was obtained from the vastus lateralis or peroneus brevis muscles of 34 healthy volunteers. Focal and extensive areas of Z band streaming and disruption of myofibrillar architecture without Z band streaming were quantified in Araldite-embedded specimens examined in the phase microscope. Extensive areas of Z band streaming in more than 2.0 percent of fibers was present in only two of the 34 volunteers. Myofibrillar disruptions without Z band streaming was much less common than Z band stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 0 publications
4
11
1
Order By: Relevance
“…Similar ultrastructural alterations have been re ported earlier [16,31,34], The disorganisa tion in the internal architecture of fibers in the localized areas is taken to be a nonspe cific indicator of damage, and has been re ported in normal human subjects [26]. In the present study, in addition to the findings described above, there were varied mito chondrial alterations.…”
Section: Discussionsupporting
confidence: 89%
“…Similar ultrastructural alterations have been re ported earlier [16,31,34], The disorganisa tion in the internal architecture of fibers in the localized areas is taken to be a nonspe cific indicator of damage, and has been re ported in normal human subjects [26]. In the present study, in addition to the findings described above, there were varied mito chondrial alterations.…”
Section: Discussionsupporting
confidence: 89%
“…Z band abnormalities have been described in a num ber of diseases [12] such as central core disease, Schwartz-Jampel syndrome, myotonic dystrophy, poly myositis, dermatomyositis, and inclusion body myositis [3]. There is experimental evidence that Z band stream ing is associated with ischemia [8]; the presence of this streaming and a scalloped surface in the affected fibers of our cases suggests the possibility of an ischemic process.…”
Section: Discussionsupporting
confidence: 50%
“…Hypercontracted ®bers have been noted in dystrophic muscle, although in general other signs of degeneration and necrosis are also observed (Cullen and Fulthorpe 1975;Schmalbruch 1973Schmalbruch , 1975. As noted above, hypercontracted ®bers are typically not present in muscle samples obtained by open biopsy from healthy individuals (Meltzer et al 1976;Moulds et al 1977;Schmalbruch 1973Schmalbruch , 1975. A high [Ca 2+ ] has been implicated in the hypercontraction and degeneration noted in diseased skeletal muscle (Oberc and Engel 1977;Schmalbruch 1975;Tay et al 1992).…”
Section: Eccentric Muscle Actionsmentioning
confidence: 97%
“…In the open biopsy technique, large muscle samples (@2±3 cm in length, 0.5 cm 2 in cross-section) can be obtained and are often clamped prior to excision, thus helping to prevent hypercontraction (Bossen 2000;Moulds et al 1977;Schmalbruch 1975). Hypercontracted ®bers have either not been observed (Meltzer et al 1976;Moulds et al 1977;Schmalbruch 1975), or have been observed only rarely in healthy muscle samples obtained by open or surgical biopsy (Schmalbruch 1973). In muscle samples obtained by open biopsy from healthy subjects, Moulds et al (1977) reported hypercontraction only at the cut ends of muscle ®bers.…”
Section: Possible Sources Of Muscle ®Ber Hypercontractionmentioning
confidence: 99%